2019
DOI: 10.1186/s13046-019-1358-x
|View full text |Cite
|
Sign up to set email alerts
|

DTL promotes cancer progression by PDCD4 ubiquitin-dependent degradation

Abstract: Background Ubiquitin E3 ligase CUL4A plays important oncogenic roles in the development of cancers. DTL, one of the CUL4-DDB1 associated factors (DCAFs), may involve in the process of cancer development. Programmed cell death 4 (PDCD4) is a tumor suppressor gene involved in cell apoptosis, transformation, invasion and tumor progression. Methods Affinity-purification mass spectrometry was used to identify potential DTL interaction proteins. Co-immunoprecipitation (Co-IP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 46 publications
1
56
0
Order By: Relevance
“…DTL (denticleless E3 ubiquitin protein ligase homolog) is an ubiquitin-related protein that was reported to contribute to the migration, invasion and poor prognosis of cancer 53 by inducing the degradation of programmed cell death 4. 54 Low expressed miR-508-3p was demonstrated to be significantly associated with distant metastasis. 55 Ectopic expression of miR-508-3p significantly suppressed the invasion ability of cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…DTL (denticleless E3 ubiquitin protein ligase homolog) is an ubiquitin-related protein that was reported to contribute to the migration, invasion and poor prognosis of cancer 53 by inducing the degradation of programmed cell death 4. 54 Low expressed miR-508-3p was demonstrated to be significantly associated with distant metastasis. 55 Ectopic expression of miR-508-3p significantly suppressed the invasion ability of cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…CENPE functioned as an oncogene and promoted the progression of various types of cancers including lung cancer, esophageal adenocarcinoma, and prostate cancer. [17][18][19] DTL was found to promote cancer progression by PDCD4 ubiquitin-dependent degradation 20 and DTL depletion inhibited liver cancer cell growth, increased senescence, and reduced tumorigenesis. 21 FANCI was functioned as a DNA-repair protein and has been found to be involved in the breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, DTL overexpression decreased the protein level and accelerated the degradation rate of PDCD4 by ubiquitination and in cancer tissues was significantly upregulated than in normal tissues [32]. Moreover, cancer patients with higher DTL expression owned lower survival rate, and functional experiments found that DTL enhanced the motility and proliferation of cancer cells through degrading PDCD4 to promote the development of cancers [32]. A recent study showed that DTL, as one of the nine hub genes, played a role in type 2 diabetes mellitus and hepatocellular carcinoma (HCC) [33].…”
Section: Discussionmentioning
confidence: 98%
“…PEST domain of AHCYL2 interacts with the NBCe1-B, which plays a critical role in neuronal modulation and intracellular pH regulation during activity [30,31]. Reportedly, DTL overexpression decreased the protein level and accelerated the degradation rate of PDCD4 by ubiquitination and in cancer tissues was significantly upregulated than in normal tissues [32]. Moreover, cancer patients with higher DTL expression owned lower survival rate, and functional experiments found that DTL enhanced the motility and proliferation of cancer cells through degrading PDCD4 to promote the development of cancers [32].…”
Section: Discussionmentioning
confidence: 99%